Polish expert group recommendations for RSV vaccination in adults - Nitsch-Osuch, Aneta; Antczak, Adam; Barczyk, Adam; Czupryniak, Leszek; Grabowski, Marcin; Kupczyk, Maciej; Ledwoch, Justyna; Mastalerz-Migas, Agnieszka; Sutkowski, Michał; Szymański, Filip; Wysocki, Jacek (Family Medicine & Primary Care Review, 2024)
Respiratory syncytial virus (RSV) causes acute lower and upper respiratory tract infections in all age groups. The clinical course of RSV infection differs depending on age and comorbidities. RSV infections are severe in the adult population; the highest risk of complications is seen in the elderly (age over 60 years) and in individuals with certain chronic disorders. Vaccination is the only currently available method of active prevention of RSV infections in adults. RSV vaccines stimulate both the humoral and the cell-mediated immunity and ensure a high level of protection against severe and complicated infection. Vaccination is recommended in all patients over the age of 60 years, particularly those with chronic disease (asthma, chronic obstructive pulmonary disease and other chronic respiratory tract disorders, ischaemic heart disease, heart failure, cardiac arrhythmias, diabetes, chronic kidney disease), immunodeficient individuals and nursing home residents.